Perencanaan Pembelajaran Pendidikan Agama Islam di Pesantren Darul Mizan Bogor - Malik Ibrohim; Endin Mujahidin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The learning process is very important in the world of education. Applying appropriate and good learning will make it easier to achieve learning goals. For this reason, good planning is needed in learning to achieve good results. There are many challenges and problems faced by a teacher in the Islamic Religious Education learning process, including the large number of students who are not interested in studying PAI, because the material taught seems boring, especially metaphysical material, but this can be overcome with careful planning and measurable. The importance of learning planning can be a solution to the problems and challenges faced by teachers in the PAI learning process, making it easier for each teacher to carry out the learning process in order to achieve the learning goals that have been set.